A two-fold interpenetration pillar-layered metal-organic frameworks based on BODIPY for chemo-photodynamic therapy. (April 2021) - Meng, Yang; Du, Yingying; Lin, Yanxin; Su, Yu; Li, Ruonan; Feng, Yaqing; Meng, Shuxian
Abstract: The combination of chemotherapy and photodynamic therapy has been proved to be a promising therapy for drug-resistant cancers. In this study, we report, for the first time, a novel two-fold interpenetration pillar-layered metal-organic frameworks (MOFs) material, using BODIPY-derivate bipyridine as linker and Photosensitizer (PS), named BBP-MOFs, was successfully synthesized to serve as a drug carrier and Photodynamic agent simultaneously. The BBP-MOFs could generate singlet oxygen ( 1 O2 ) to perform PDT under 660 nm light irradiation, in the meantime, the anticancer drugs doxorubicin (DOX) could be loaded for chemotherapy. The results showed that BBP-MOFs exhibited a high drug loading content of 49.7% a controlled drug release and ideal biocompatibility. This DOX loaded BBP-MOFs was readily taken up by HeLa cells, and high levels of 1 O2 were generated under light irradiation. This work provided strong evidence for BBP-MOFs as a promising new anticancer drug carrier and PDT candidate, the PDT and chemotherapy combined synergistic therapy revealed high therapeutic efficacy for cancer cells. Highlights: A novel two-fold interpenetration pillar-layered metal-organic frameworks (MOFs) material. The combination of DOX-mediated chemotherapy and BBP-MOFs-based PDT. BBP-MOFs exhibited a high drug loading and ideal biocompatibility.